The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/w12061549
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ensembles of Deep Learning Neural Network and Statistical Learning for Flash-Flood Susceptibility Mapping

Abstract: This study aimed to assess flash-flood susceptibility using a new hybridization approach of Deep Neural Network (DNN), Analytical Hierarchy Process (AHP), and Frequency Ratio (FR). A catchment area in south-eastern Romania was selected for this proposed approach. In this regard, a geospatial database of the flood with 178 flood locations and with 10 flash-flood predictors was prepared and used for this proposed approach. AHP and FR were used for processing and coding the predictors into a numeric format, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 60 publications
(88 reference statements)
1
23
0
Order By: Relevance
“…In the present study, with the help of the FFPI method, we provided a way to determine floods in hydrologically unmonitored areas, thus covering a dysfunction mentioned in numerous studies that aimed to model the risk of flooding (Costache 2019b;Costache et al 2020;Minea 2013;Popa et al 2020;Zeng et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, with the help of the FFPI method, we provided a way to determine floods in hydrologically unmonitored areas, thus covering a dysfunction mentioned in numerous studies that aimed to model the risk of flooding (Costache 2019b;Costache et al 2020;Minea 2013;Popa et al 2020;Zeng et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Remote Sens. 2021, 13, x FOR PEER REVIEW 3 that have made contributions in this regard [27,28]. The common conclusion of the a studies of hybrid models is that these hybrid models have improved flood suscept prediction capabilities.…”
Section: Materials 21 Study Areamentioning
confidence: 99%
“…Tehrany et al integrated the weights-of-evidence and four kernel types of SVM in flood susceptibility mapping in Terengganu, and found that the WoE-RBF-SVM showed the best performance [26]. In addition, there are a lot of studies that have made contributions in this regard [27,28]. The common conclusion of the above studies of hybrid models is that these hybrid models have improved flood susceptibility prediction capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Along with its high support for flood and flash-flood early warning systems, the high-accurate estimation of flood exposed areas can also help to draw up the river basins flood defence plans (Albano et al 2017;Johann and Leismann 2017;Brillinger et al 2020). The following models are among the most popular ML algorithms used to estimate the flood susceptibility: Artificial Neural Network (ANN) (Costache et al 2020b), support vector machine (SVM) (Nguyen et al 2017;Tehrany et al 2019;Sahana et al 2020), decision trees-based models (Chen et al 2018;Khosravi et al 2018;Costache 2019c), naïve Bayes (Ali et al 2020;Tang et al 2020), deep learning neural network (Costache et al 2020a), extreme learning machine (Tang et al 2020). All the models applied in the above works achieved an accuracy higher than 80%.…”
Section: Introductionmentioning
confidence: 99%